Research of Carthamus tinctorius L. F1 hybrids in the conditions of the Northern Caspian region - N. A. Zaitseva; S. V. Zaitsev (Аграрная наука Евро-Северо-Востока, 2024)
Safflower (Carthamus tinctorius L.) is an oilseed crop characterized by high drought tolerance. In conditions of increasing climate aridisation in Russia, especially in the southern regions, agricultural producers are becoming interested  in this crop. It is especially important to develop new varieties capable of producing stable yields even in severely arid regions. Experiments were laid in 2022-2023 in the conditions of the Astrakhan region. They studied Carthamus tinctorius L. F1 hybrids which were obtained from crossing seven promising varieties selected from the collection of FRC N. I. Vavilov  All-Russian Institute of Plant Genetic Resources (VIR) and two varieties developed at the Precaspian Agrarian Federal Scientific Centre. Preliminary self-pollination of parental pairs was carried out for three years using insulators made of non-woven material, which allows air to pass through, but does not allow insects and pollen to pass through. Crossing was carried out in 2022 according to the method of T. V. Leus and E. V. Vedmedeva (2013) using pollen flushing followed by pollination for three days. In 2023, seeds of F1 hybrids obtained by crossing were sown in a wide-row method on 2 m2 plots for their economic and biological evaluation and comparison with parents. On the basis of the obtained data, promising hybrids (prickly) were identified, which exceeded the parental pairs in yield and oil content: 1/22 (from crossing Oker x Astrakhansky 747) – by 0.18–0.20 t/ha and 3-4 abs.%; 4/22 (ʻCentre 70ʼ x ʻAstrakhansky 747ʼ) – by 0.11–0.29 t/ha and 6 abs.%, respectively. Among non-spiny hybrids, the following hybrids stood out: 5/22 (ʻShahalli-260ʼ x ʻAstrakhansky 646ʼ), 9/22 (ʻTsambuliʼ x ʻShirkasʼ), 7/22 (ʻTsambuliʼ x ʻAstrakhansky 646ʼ), yields of which exceeded parental pairs by 0.17–0.72 t/ha, oil content – by 1–5 abs.%.